Factors contributing to the timely completion of PhD at the Malaysian public higher educational institutions - Mohd Shariff, Nurhazani; Ramli, Kamal Izzuwan; Ahmad, Rozila; Zainol Abidin, Azlan (ARC Publications Pvt Ltd, 2015)
This study investigated the perceptions of PhD candidates on factors contributing to the timely completion of PhD at the Malaysian Public Higher Educational Institutions. The study focused on six factors namely supervision arrangements factor, research skills factor, research work factor, institutional factor, motivational factor and de-motivational factor.320 PhD candidates from Universiti Utara Malaysia were selected as respondents.The data gained were then statistically analyzed using descriptive statistics analysis.The findings revealed that the PhD candidates perceived research skills factor as the most contributing factor to the timely completion of their study.Supervision arrangements factor was considered as the second factor contributing to the timely completion of their PhD, followed by motivational factor, demotivational factor and institutional factor. Eventually, the PhD candidates found that research work factor did not highly contribute to the timely completion of their PhD.The study significantly provides the institution specifically in the case of Malaysian Public Higher Educational Institutions with accurate factors which they need to consider in order to effectively planning and managing the postgraduate candidates for completing their PhD within the time frame.